English Learning Strategies based on Artificial Intelligence (AI) - Desmiyanti, Desmiyanti (JELT: Journal of English Language Teaching, 2025)
Mastering English is needed to face the era of globalization. English plays a strategic role in international communication, both technology and education. This study aimed to explore English learning strategies based on Artificial Intelligence (AI). By using a literature study through a descriptive qualitative approach, this study was expected to provide comprehensive results. The results of this study indicated that AI-based English learning strategies offered a more interactive and personal approach to developing students' language skills. One of the commonly used an AI-based learning platform such as an AI-based virtual assistant.  For instance, Duolingo, Grammarly and ChatGPT which can facilitate English speaking and listening practice. Meanwhile, English learning based on Artificial Intelligence (AI) technology has a number of challenges that need to be considered in its implementation, both in terms of technical, pedagogical, and social aspects. The first challenge that is often faced was the limited ability of AI to understand the context and the nuances of language in depth. English has grammatical and idiomatic complexities that are often difficult for AI systems to understand. Although AI can perform syntactic and semantic analysis, understanding meaning in the context of a broader conversation or text was still remains a challenge